Studies on the Flexible Epoxy Resin Curing Agent - Wang, X.; Qi, D.T. (Asian Journal of Chemistry, 2013)
Epoxy resin structural adhesives modified by flexible curing agent. Dependening on the mechanical properties of epoxy resins on the flexible curing agent content was studied. The impact fracture toughness was discussed in terms of fracture surface fractography.